The THE EFFECT OF LITERACY, POPULATION DENSITY, AND EDUCATION ON UNEMPLOYMENT IN ASEAN FROM AN ISLAMIC ECONOMIC PERSPECTIVE - David, Juand Trika; Putri, Rosydalina; Malik, Anas (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Unemployment is one of the enduring macroeconomic issues that both developed and emerging nations, including those in ASEAN, must deal with. The purpose of this study is to examine, from an Islamic economic perspective, how unemployment rates in 10 ASEAN countries relate to literacy, population density, and educational achievement. Panel data from the 10 ASEAN nations for 2018–2024, obtained from the World Bank and the ASEAN Statistical Annual, is used in this research using a saturation sampling technique. The data was analyzed using EViews 12 software at a significance level of α=0.05. According to the research findings, literacy levels have a considerable positive impact on unemployment rates in the ten ASEAN countries, whereas population density and educational attainment had little effect. At the same time, population density, education levels, and literacy levels all have a big impact on unemployment rates. In Islamic economics, unemployment is seen as a social and economic problem that is contrary to the principles of justice and welfare of the maqashid sharia, especially the preservation of life and property.